The study of gangrenous large bowel in COVID-19 patient in our institute an observational study - Bhusakhare, Niraj; Singh, Rahul; Singh, Vinod; Goyal, Sanjay; Marhual, Jogesh Chandra; Kathale, Samir (International Surgery Journal, 2022)
Initially considered to be a respiratory disease, COVID-19 is now recognized as a multisystem disease known to affect all the major organs, including the gastrointestinal system. Based on recent studies, coronavirus 2 causes dysregulation of multiple biological pathways, triggers an exaggerated immune response, and affects multiple organs. The gastrointestinal symptoms in COVID-19 are common but often overlooked. This is an observational study analyzing the clinical characteristics and outcomes of three COVID-19 patients aged 80-year, 75-year, 69-year presented to our institution from April 2021 to June 2021 and were diagnosed with COVID-19 and subsequently develop perforation peritonitis and gangreneos large bowel as a first presentation. All patients tested COVID-19 positive upon admission and received standard care.